2021
DOI: 10.3390/su13105713
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Macroeconomic, Social and Governance Factors on the Sustainability and Well-Being of the Economic Environment and the Robustness of the Banking System

Abstract: The paper highlights the connection between the European Union banking system and a set of representative factors—macroeconomic, social, and governance factors—selected from the perspective of sustainability and well-being. The analysis is carried out as a panel regression on EU member countries with annual data for 2005–2018, and it explores the impact of the selected factors on the robustness of the banking systems in the European Union countries. The analyzed variables to reflect the robustness of the banki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Social issues increase socioeconomic risk and financial crisis [22]. Social inequality decreases the effectiveness of the banking industry as it decreases access to credit [13]. Ng et al [43] has confirmed easy credit availability at a reasonable rate for improving the infrastructure to increase the health and education facility can increase the economic opportunities for poor people and the quality of their life.…”
Section: Social Sustainability and Nonperforming Loansmentioning
confidence: 99%
“…Social issues increase socioeconomic risk and financial crisis [22]. Social inequality decreases the effectiveness of the banking industry as it decreases access to credit [13]. Ng et al [43] has confirmed easy credit availability at a reasonable rate for improving the infrastructure to increase the health and education facility can increase the economic opportunities for poor people and the quality of their life.…”
Section: Social Sustainability and Nonperforming Loansmentioning
confidence: 99%
“…Investigators of the influence of the environment on the stability of the relevant banking system have pointed to a number of external factors likely to destabilise the banking system (Dedu, Dan-Costin, and Cristea, 2021). It allows them to assess the systemic risk, i.e., the risk of disruption in the whole financial system (including the banking system) of a country due to an external shock (Danielsson, James, Valenzuela, and Zer, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%